HLA-DQB1/DRB1 Alleles Associate with Traditional Chinese Medicine Syndrome of Chronic Hepatitis B: A Potential Predictor of Progression. (21st November 2019) - Liu, Xiyang; Wan, Tingjun; Dang, Sijie; Wang, Dong; Jiang, Cen; Su, Yue; Shen, Mengmeng; Tang, Xuchen; Li, Xia; Li, Baixue; Wen, Li; Feng, Quansheng
Abstract : Background and Aims . Traditional Chinese medicine (TCM) has been widely applied in chronic hepatitis B (CHB) supplementary treatment in China. Kidney yang deficiency syndrome (KYDS), one of the most common TCM syndromes of CHB, is more likely to progress to liver cirrhosis or hepatocellular carcinoma than other syndromes. Polymorphisms in the human leucocyte antigen- (HLA-) DQB1 and -DRB1 genes were reported to be associated with hepatitis B virus infection outcomes. Here, we investigated whether HLA-DQB1 and HLA-DRB1 are associated with the classification of CHB TCM syndromes. Methods . We genotyped HLA-DQB1 and HLA-DRB1 alleles in a total of 105 subjects, including 74 CHB patients (28 KYDS and 46 non-KYDS) and 31 healthy individuals from Sichuan Province of Southwest China, by polymerase chain reaction sequence-based typing (PCR-SBT). Moreover, a meta-analysis was carried out for further verification. Results . The proportion of patients with high HBV DNA load (≥2000 IU/ml) in the KYDS group is higher than that in the non-KYDS group (60.70% [17/28] vs. 28.30% [13/46]); P = 0.01 ). The frequencies of HLA-DQB1 ∗ 02 : 01 (P = 0.04 ) and HLA-DRB1 ∗ 03 : 01 (P = 0.04 ) in the KYDS group were significantly increased compared to the non-KYDS group. The gene test and meta-analysis showed that HLA-DRB1 ∗ 08 : 03 confers susceptibility to CHB (odds ratio = 1.57). Conclusion . We found an association between HLA-DRB1 / DQB1 polymorphisms and KYDS of CHB. Moreover, KYDS patients of CHB are characteristic with high HBV DNA loads. These findings help to reveal the biological mechanism of KYDS in high risk of CHB progression and suggest a potential prognostic value for disease outcome evaluation.